2012
DOI: 10.1603/ec11318
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Demography of <I>Aulacaspis yasumatsui</I> (Hemiptera: Diaspididae)

Abstract: Aulacaspis yasumatsui Takagi continues to threaten the extinction of the endemic and endangered Cycas taitungensis (Shen et al.) in Taiwan. Failure to understand its population demographic parameters in detail will continue to hinder the success of pest management practices. An in-depth knowledge of the development, survival, and fecundity of A. yasumatsui under different environmental conditions is necessary to understand its' population growth. The demography of A. yasumatsui was studied in the laboratory ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous results have demonstrated that CAS eggs hatch to nymphs in 8–12 days when the temperature is 24.5 °C ( Howard et al, 1999 ) and adult female would be not laid eggs when temperature at 18 °C and 35 °C ( Cave, Sciacchetano & Diaz, 2009 ). Moreover, 25 °C–28 °C has been confirmed to be the most suitable temperature range for the development and reproduction of CAS ( Ravuiwasa et al, 2012 ). However, temperatures below 15 °C have been shown to be unsuitable for this insect, as indicated by the high mortality observed in laboratory research ( Teaaro, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have demonstrated that CAS eggs hatch to nymphs in 8–12 days when the temperature is 24.5 °C ( Howard et al, 1999 ) and adult female would be not laid eggs when temperature at 18 °C and 35 °C ( Cave, Sciacchetano & Diaz, 2009 ). Moreover, 25 °C–28 °C has been confirmed to be the most suitable temperature range for the development and reproduction of CAS ( Ravuiwasa et al, 2012 ). However, temperatures below 15 °C have been shown to be unsuitable for this insect, as indicated by the high mortality observed in laboratory research ( Teaaro, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This life table theory takes the stage differentiation and male population into consideration. The age-stage, twosex life table theory has been applied to insect and mite species by a number of researchers (Abou Zied et al 2003, Gabre et al 2005, Kavousi et al 2009, Hu et al 2010, Farhadi et al 2011, Jin et al 2012, Ravuiwasa et al 2012, Azimi et al 2013, Yu et al 2013, Zare et al 2013.…”
mentioning
confidence: 99%
“…The second study was conducted in Taiwan using C. taitungensis as the host [9]. At a constant temperature of 24 One more study in Taiwan used C. revoluta as the host and employed a range of temperatures [10]. The optimum temperature was found to be 28 • C, resulting in an egg incubation time of 7.8 d. The durations of other stages were similar to previous reports; for females, the total development time from egg to adult was 36.8-59 d. and maximum longevity was 44.7-57.4 d. For males, duration of the adult stage was 1.5-2.1 d. The net reproduction rate per adult female ranged from 46 offspring at sub-optimal temperatures to 96 at optimal temperatures.…”
Section: Life Historymentioning
confidence: 99%
“…Temperature-response studies [8,10] revealed that sub-optimal and supra-optimal temperatures were highly effective in reducing reproductive performance in A. yasumatsui. However, conservationists cannot rely on temperature extremes to eradicate this cycad pest, because it survives them even if it does not reproduce well at these temperatures.…”
Section: Knowledge Of Temperature Responses May Aid Cycad Conservationmentioning
confidence: 99%